Optimizing the Automation in Construction Site Logistics: Problems and Propsed Modell Library for Materials Flow Simulation - Schlosser, Alexander; Barth, Martin; Schuderer, Peter; Franke, Jörg (2024)
The construction industry is currently facing challenges such as skilled labor shortages, limited automation, and inadequate digitalization, particularly for small and medium-sized enterprises (SME), amidst rising interest rates and decreasing subsidies for builders. To address these challenges, a simulation model library for construction is being established. The Plant Simulation System is used to map construction site systems with various model components, enabling digital simulation of the environment and supply chains. Customized simulation parameters are used to simulate specific construction requirements. This paper describes the use of masonry robots and transportation in wall and floor construction and their impact on site performance. The simulation model library REMUS is important for digitalizing construction sites, allowing for the assessment of innovative systems before construction and estimation of investment returns. Simulations can be used to evaluate investments and future concept
Keywords: Automation; Economic indicators; Supply chains; Transportation; Estimation; Libraries; Robots; Optimization; Floors; Investment